Effects of a targeted multimodal exercise program incorporating high-speed power training on falls and fracture risk factors in older adults: A community-based randomised controlled trial - Gianoudis, J.; Bailey, C.; Ebeling, P.; Nowson, C.; Sanders, K.; Hill, Keith; Daly, R. (American Society for Bone and Mineral Research, 2014)
Multimodal exercise programs incorporating traditional progressive resistance training (PRT), weight-bearing impact training and/or balance training are recommended to reduce risk factors for falls and fracture. However, muscle power, or the ability to produce force rapidly, has emerged as a more crucial variable to functional decline than muscle strength or mass. The aim of this 12-month community-based randomized controlled trial, termed Osteo-cise: Strong Bones for Life, was to evaluate the effectiveness and feasibility of a multimodal exercise program incorporating high-velocity (HV)-PRT, combined with an osteoporosis education and behavioral change program, on bone mineral density (BMD), body composition, muscle strength and functional muscle performance in older adults. Falls incidence was evaluated as a secondary outcome. A total of 162 older adults (mean ± SD; 67 ± 6 years) with risk factors for falls and/or low BMD were randomized to the Osteo-cise program (n = 81) or a control group (n = 81). Exercise consisted of fitness center-based HV-PRT, weight-bearing impact and challenging balance/mobility activities performed three times weekly.After 12 months, the Osteo-cise program led to modest but significant net gains in femoral neck and lumbar spine BMD (1.0% to 1.1%, p < 0.05), muscle strength (10% to 13%, p < 0.05), functional muscle power (Timed Stair Climb, 5%, p < 0.05) and dynamic balance (Four Square Step Test 6%, p < 0.01; Sit-to-Stand, 16%, p < 0.001) relative to controls. There was no effect on total body lean mass or mobility (timed-up-and-go), and no difference in falls rate (incidence rate ratio [IRR], 1.22; 95% confidence interval [CI], 0.72–2.04). In conclusion, this study demonstrates that the Osteo-cise: Strong Bones for Life community-based, multimodal exercise program represents an effective approach to improve multiple musculoskeletal and functional performance measures in older adults with risk factors for falls and/or low BMD. Although this did not translate into a reduction in the rate of falls, further large-scale trials are needed to evaluate the efficacy of this multimodal approach on reducing falls and fracture.